BIOMECHANICAL ANALYSIS OF DISCUS THROWING IN FEMALE ATHLETES: A COMPREHENSIVE REVIEW - Yuldasheva Kamola Alimjanovna (Research Focus International Scientific Journal, 2024)
Discus throwing, a pivotal event in track and field athletics, demands precise biomechanical execution to achieve optimal performance. This comprehensive review delves into the biomechanical intricacies of discus throwing with a specific focus on female athletes. By analyzing critical elements such as body posture, release technique, force generation, and energy transfer, the study aims to enhance the understanding of female-specific biomechanical factors influencing discus performance. Utilizing advanced motion capture technology and high-speed video analysis, this review uncovers key biomechanical determinants that impact the effectiveness of the throw. The review systematically examines the following aspects: Body Posture and Alignment: Assessing the influence of initial stance, wind-up mechanics, and body alignment on the throw's efficiency. Release Technique: Investigating the role of grip, release angle, arm extension, and wrist action in optimizing throw distance. Force Generation and Energy Transfer: Exploring the impact of leg drive, hip rotation, and core engagement on the transfer of force to the discus. Data from biomechanical studies involving female athletes across varying skill levels (novice, intermediate, and elite) are reviewed to highlight differences in performance metrics such as release speed, force, hip rotation, and energy transfer. The review integrates findings from highspeed cameras and 3D motion capture systems, providing a detailed analysis of how these factors correlate with performance outcomes. Key findings indicate that elite female discus throwers exhibit significantly higher release speeds, greater force generation, improved hip rotation, and more efficient energy transfer compared to novice and intermediate throwers. These differences underscore the importance of advanced technique, enhanced biomechanical coordination, and effective training regimens tailored to improve specific aspects of the throwing technique.